Perception of extractivists about the Mauritia flexuosa palm swamp in the Lençóis Maranhenses Region, Brazil - Irlaine Rodrigues Vieira (Sociedade & Natureza, 2019)
Researches of environmental perception evidences the extractive context and help policy making. Despite the social and economic benefits, the intensification of extractivism can promote ecological unsustainability and alteration in the perception of forest conservation values. In the region of Lençóis Maranhenses, Northeast Brazil, the sale of products extracted from Mauritia flexuosa L.f palm to supply the local and national market is increasing. Thus, we aimed to evaluate the forest values perceived by extractivists in municipalities of the region of Lençóis Maranhenses and how the socioeconomic profile interfere with the environmental perceptions of the interviewees. The research was conducted through semi-structured forms applied to 271 extractivists from the municipality of Barreirinhas, Paulino Neves and Tutóia. The perceived forest values were divided into three categories: economic, ecological and social. It was contacted that there was a prioritization of the values included in the Economic category, in which the source of income is highlighted in the municipalities that most extract the palms. The data revealed that there was a prioritization of the economic category, with emphasis on the forest value source of income. In Barreirinhas, food and climate regulation values were related to socioeconomic characteristics such as gender and monthly income from the sale of handicrafts. There is knowledge about the environmental damages that occur in the forest. However, there is no effective participation of the communities in the management of the Environmental Conservation Units of the region.